Risk factors associated with developmental abnormalities among high-risk children attended at a multidisciplinary clinic - Resegue, Rosa; Puccini, Rosana Fiorini; Silva, Edina Mariko Koga da (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Knowledge of risk factors associated with child development disorders is essential for delivering high-quality childcare. The objective here was to evaluate the relationships between risk factors and occurrences of developmental abnormalities among children attended at a reference clinic for children at risk of developmental abnormalities. DESIGN AND SETTING: Retrospective study at a multidisciplinary reference center, Embu, São Paulo. METHODS: All cases followed up for more than three months between 1995 and 2003 were reviewed. The risk factors assessed were low birth weight, gestational age, length of stay in neonatal ward, perinatal asphyxia, mother’s age < 18 years, congenital infections, malformations and low mother’s education level. Developmental abnormalities were defined according to developmental tests and assessments by the clinic’s professionals. The statistical analysis consisted of the chi-squared test for comparing categorical variables and a logistic regression model for multivariate analysis. RESULTS: 211 children were followed up for more than three months. Developmental abnormalities occurred in 111 (52.6%). Univariate analysis showed significant relationships between developmental abnormality and low birth weight, perinatal asphyxia, length of stay > 5 days, prematurity and mother’s age 18 years and older. Low birth weight, history of perinatal asphyxia and mother’s age continued to be significant in multivariate analysis. CONCLUSIONS: Special attention must be paid to the development of low birth weight infants and/or infants with histories of neonatal complications. Low birth weight is easily assessed and should be considered to be an important marker when defining guidelines for following up child development.